A special grease for open gear of rod mill and its preparation method
Patent Information
- Application Number
- CN202311554825.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-21
AI Technical Summary
Lubrication failure of open gears in rod mills leads to tooth surface damage, fatigue cracks, wear pitting, and corrosion, affecting the service life of the equipment.
The grease is formulated with a specific combination of components including base oil, fatty acids, aromatic acids, trimers, solid waxes, solid extreme pressure agents, metal powders, rust inhibitors, metal deactivators, tackifiers, and other ingredients. It is prepared by a stepwise reaction method to ensure good tooth surface adhesion, water resistance, and low-temperature pumpability.
It effectively extends the service life of equipment, reduces tooth surface wear, prevents corrosion, improves lubrication, reduces vibration of transmission motor bearings, and optimizes the force distribution on the tooth surface.
Smart Images

Figure BDA0004560690870000071 
Figure BDA0004560690870000072 
Figure BDA0004560690870000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of lubricating grease technology, and in particular to a special lubricating grease for open gears of rod mills and its preparation method. Background Technology
[0002] Rod mill grease is used for lubricating open gear components under low-speed, heavy-load, and high-impact conditions. Currently available open gear lubricants include high-viscosity oils, asphalt-based lubricants, solid-based lubricants, and compound lubricants. These types are commonly used in open gear components and can meet the tooth surface lubrication requirements under normal operating conditions. Large open gears are often selected as the main drive unit of equipment, and their surfaces frequently suffer various forms of damage, such as fatigue wear, scratches, scuffing, and pitting. This can lead to metal loss from the tooth surface, altering the gear's geometry and severely impacting the equipment's service life.
[0003] During long-term production, the vibration of the steel bars running inside the rod mill cylinder causes the cylinder bolts to loosen, which in turn causes the sealing rubber and sealing ring rolls to deform, resulting in seal failure. The slurry leaks into the gear cover, destroying the contact oil film of the large and small gears. Particulate matter wears on the tooth surface, causing tooth surface damage, fatigue cracks, and wear pitting. In addition, the tooth bottom surface is in long-term contact with the slurry, and the rust prevention performance of the lubricating grease is insufficient, which in turn leads to tooth surface corrosion. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a special grease for open gears of rod mills, so as to solve the problem of lubrication failure of open gears in rod mills.
[0005] To achieve the above objectives, the present invention employs the following technical solution:
[0006] A special lubricating grease for open gears of rod mills, wherein the lubricating grease comprises, by weight percentage:
[0007] Base oil: 55%–65%;
[0008] Fatty acid: 1.05%–1.47%; it is stearic acid with a melting point of 69–72°C.
[0009] Aromatic acid: 0.45%–0.63%; the aromatic acid is benzoic acid with a melting point of 122–123℃;
[0010] Trimer: 0.86%–1.21%; the trimer is triisopropanol aluminum trioxide;
[0011] Solid wax: 2%–3%; solid wax is microcrystalline wax with a melting point of 80–85℃;
[0012] Solid extreme pressure agent 1: 10%–13%;
[0013] Solid extreme pressure agent 2: 1% to 2%;
[0014] Metal powder: 2-3%; the metal powder is a mixture of aluminum powder with a particle size of 10μm-20μm and zinc powder with a particle size of 3μm-4μm in a mass ratio of 2:1;
[0015] Rust inhibitor: 1%–1.5%;
[0016] Metal deactivating agent: 0.1%–0.5%;
[0017] Tackifier: 12%–20%.
[0018] The base oil is a mixture of paraffinic base oil and polyalphaolefin base oil, with a kinematic viscosity of 700–850 mmHg at 40°C. 2 / s.
[0019] The solid extreme pressure agent 1 is S-0 flake graphite with a particle size of <1μm.
[0020] The solid extreme pressure agent 2 is a 1,3,4-thiadiazole substituted derivative.
[0021] The rust inhibitor is one or a mixture of both of petroleum ester barium soap and zinc oxide.
[0022] The metal deactivator is a benzotriazole derivative.
[0023] The thickener is a metallocene-catalyzed ethylene-propylene copolymer, NacoTac2008.
[0024] A method for preparing a special lubricating grease for open gears of a rod mill includes the following steps:
[0025] 1) Premixed base oil;
[0026] 2) Thickening reaction: Transfer 60% to 70% of the premixed base oil into the reactor, add trimer, start bidirectional stirring and bottom stirring, add fatty acids at 80 to 85°C, keep the temperature at 86 to 92°C for 20 to 30 minutes, add aromatic acid at 115 to 120°C, keep the temperature at 125 to 130°C for 30 to 40 minutes.
[0027] 3) High-temperature refining: Heat the material from step 2) to 155-160℃, keep it at that temperature for 5-10 minutes, add the thickener, stir for 15-20 minutes, transfer it from the homogenizer to the mixing tank to obtain high-viscosity composite aluminum soap;
[0028] 4) Melting microcrystalline wax: Control the temperature of the material in step 3) to 100-105℃, add microcrystalline wax, and stir to melt for 20-25 minutes;
[0029] 5) Dispersing solids: Cool the material from step 4) to 85-90°C, add solid extreme pressure agent 1 and solid extreme pressure agent 2, stir and mix, and filter step by step;
[0030] 6) Mixing protective agents: Cool the material from step 5) to 80-85℃, add rust inhibitor and metal deactivator, and stir for 10-15 minutes;
[0031] 7) Add metal powder: Cool the material from step 6) to 30-50℃, add metal powder, and at the same time add the remaining premixed base oil by spraying it from the top of the kettle. Mix and stir for 10-15 minutes, and filter through a 150-mesh filter for 30-40 minutes.
[0032] 8) Degassing and Packaging: Transfer the material from step 7) to the degassing kettle for degassing and packaging.
[0033] Step 1) Premixed base oil operation method: Paraffinic base oil and polyalphaolefin base oil are introduced into the base oil premixing tank through a flow meter, the temperature is controlled at 70-80℃, and the mixture is premixed and stirred for 20-30 minutes.
[0034] The high-viscosity composite aluminum soap obtained in step 3) has a dynamic viscosity of 6000–20000 mPa·s.
[0035] Step 5) Step-by-step filtration method: 80 mesh filter for 10-15 minutes, 100 mesh filter for 15-20 minutes, and 150 mesh filter for 20-30 minutes.
[0036] In step 8), the degassing pressure is -0.07 to -0.09 MPa.
[0037] Compared with existing technologies, the beneficial effects of this invention are:
[0038] In terms of base oil selection, a blend of refined paraffin-based high-viscosity mineral oil and high-viscosity synthetic hydrocarbon base oil is used to ensure the base oil viscosity and gear surface oil film thickness, while also meeting the pumping and injection requirements of the centralized lubrication system at low temperatures.
[0039] Microcrystalline wax is a refined synthetic wax with good flexibility, easy deformation under stress, and a compact structure. Its addition gives the product excellent tooth surface adhesion and water resistance. Microcrystalline wax has good oil absorption properties, and therefore also has a certain thickening ability.
[0040] Solid extreme pressure agent 1 is S-0 flake graphite, which acts as a solid lubricant under impact loads and high loads on the gear teeth, separating the surfaces of the friction pairs, thereby making the oil's load-bearing capacity stronger and more reliable. In addition, the amount of graphite adhering to the gear teeth (grayish-black) can be used to judge the stress distribution on the gear teeth. Darker color means more adhesion and greater stress, while lighter color means less adhesion and less stress. Therefore, it also has guiding significance for adjusting the flatness of large and small gears during assembly.
[0041] Solid extreme pressure agent 2 is a 1,3,4-thiadiazole substituted derivative, belonging to solid sulfide extreme pressure agents. It has good water resistance and increases the load-bearing capacity of the tooth surface under medium and heavy loads.
[0042] The metal powder is a mixture of aluminum powder (10μm-20μm particle size) and zinc powder (3μm-4μm mass ratio 2:1). It is a soft metal powder, designed to have strong adsorption capacity and repair damage to the tooth surface. The zinc powder has high density, low hardness, and small particle size, making it easier to embed into fatigue cracks on the tooth surface. The aluminum powder has large particle size, low density, and high hardness, used to adsorb and fill pitting and other wear areas on the tooth surface, preventing further damage and thus extending the equipment's service life. Aluminum powder is stable and uniformly dispersed in the material system and will not settle, while zinc powder, with its higher density, is prone to settling during storage. By controlling the aluminum-zinc powder mass ratio to 2:1, with the aluminum powder volume approximately five times that of the zinc powder, it adsorbs with the zinc powder in the oil, causing it to float and effectively preventing zinc powder settling.
[0043] The rust inhibitor is one or a mixture of barium petroleum ester soap and zinc oxide. Barium petroleum ester soap has good oil solubility, rust prevention and film-forming properties, and has good rust prevention for ferrous metals. At the same time, zinc oxide can form a dense zinc oxide film on the metal surface to protect the metal surface. Therefore, the product of this application also has excellent rust prevention effect in the environment where the tooth surface of the rod mill is in contact with water.
[0044] The tackifier is NacoTac2008, a metallocene-catalyzed ethylene-propylene copolymer. It has a high tackifier coefficient, and the expected tackifier effect can be achieved with a small amount. It also has excellent shear resistance, which is beneficial for use in the product of this application.
[0045] A composite aluminum soap thickening system is formed by using stearic acid, benzoic acid, and triisopropanol aluminum oxo. Due to its structural characteristics, the composite aluminum soap has good high-temperature reversibility and fluidity, meaning that after high temperature to room temperature, the composite aluminum soap returns to its original consistency, increasing its adhesion to the tooth surface. The grease has better consistency retention and pumpability. Compared with directly adding composite aluminum base grease, it saves 50%. The total mass of stearic acid and benzoic acid in the formula is 1.5% to 2.1% of the composite aluminum soap content in the application. If composite aluminum base grease is added directly, 3.4% to 4.2% needs to be added to achieve the same thickening effect. Therefore, this application has better economic benefits.
[0046] Microcrystalline wax is oleophilic and hydrophobic, which can inhibit the entry of environmental water into the oil, protect the viscosity and consistency from being damaged, and thus increase the adhesion of the oil to the tooth surface, which is conducive to the contact between the rust inhibitor and the tooth surface. Under the combined action of microcrystalline wax and rust inhibitor, it has excellent rust prevention effect. Based on the current application conditions of the oil, two tests were conducted: water resistance (60℃, 6 hours) and dynamic rust prevention (medium: distilled water / synthetic seawater). The results of water resistance and rust prevention were good. It has now solved the rust problem on the tooth surface of the rod mill caused by slurry leakage in the gear cover, and provides good tooth surface protection.
[0047] In terms of process, a stepwise reaction method is used to prepare composite aluminum soap, in which stearic acid and benzoic acid react with triisopropanol aluminum oxide in sequence. This method produces composite aluminum soap with a more obvious thickening effect on the system.
[0048] In terms of process, adding the thickener NacoTac2008 at high temperature is beneficial to the dispersion of polymer copolymers in materials, ensuring a uniform high-viscosity system.
[0049] In terms of process, microcrystalline wax is added at a temperature 20°C above its melting point, resulting in a finished product with a delicate and glossy appearance and optimal water resistance.
[0050] In terms of process, considering that the addition of metal powder would cause suspension within the reactor, for safety reasons, the reactor temperature was set to be lowered to 30-50℃. Aluminum and zinc powders were added, and the remaining premixed base oil was sprayed onto the top of the reactor to suppress powder suspension, controlling and reducing the concentration of metal powder mixed with air within the reactor to prevent reaching deflagration concentrations, thereby ensuring a safe production environment. Process design and formulation are complementary; any changes to the formulation or process will have a significant impact on product performance.
[0051] The grease in this application has excellent lubricity, good adhesion to tooth surfaces, good water resistance and low-temperature pumpability, and can repair tooth surface wear, pitting and fatigue cracks. It also reduces the vibration value of the transmission motor bearing, reduces the impact load on the gear meshing surface, and effectively extends the service life of the equipment. Detailed Implementation
[0052] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used herein in the specification is for the purpose of describing particular embodiments only and is not intended to limit the scope of the application. The reference to "embodiment" herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0053] A special lubricating grease for open gears of rod mills, wherein the mass percentage of each component in the lubricating grease is as follows:
[0054] Base oil: 55%–65%, wherein the base oil is a mixture of 150BS (paraffinic) and PAO100 (polyalphaolefin), with a kinematic viscosity of 700–850 mmHg at 40°C. 2 / s. The viscosity of the base oil determines the oil film thickness. Using refined paraffin-based high-viscosity mineral oil and high-viscosity synthetic hydrocarbon base oil in combination ensures both the base oil viscosity and the oil film thickness on the gear surface, while also meeting the pumping and injection requirements of the centralized lubrication system at low temperatures.
[0055] Fatty acid: 1.05% to 1.47%, wherein the fatty acid is stearic acid with a melting point of 69 to 72°C.
[0056] Aromatic acid: 0.45% to 0.63%, wherein the aromatic acid is benzoic acid with a melting point of 122 to 125°C.
[0057] Trimer: 0.86% to 1.21%, wherein the trimer is triisopropanol aluminum trioxide.
[0058] Solid wax: 2-3%, wherein the solid wax is a microcrystalline wax with a melting point of 80-85℃, which gives the product good adhesion to tooth surfaces and water resistance. The microcrystalline wax has good oil absorption properties and therefore also has a certain thickening ability.
[0059] Solid extreme pressure agent 1: 10-13%, wherein the solid extreme pressure agent 1 is S-0 flake graphite with a particle size <1μm, which plays a solid lubricating role under impact load and high load, separating the friction pair surfaces, making the oil's load-bearing capacity stronger and more reliable. In addition, the amount of graphite adhering to the tooth surface (grayish-black) can be used to judge the stress distribution on the tooth surface. Darker color, more adhesion, and greater stress; lighter color, less adhesion, and less stress. Therefore, it also has guiding significance for adjusting the flatness of large and small gears during assembly.
[0060] Solid extreme pressure agent 2: 1% to 2%, wherein the solid extreme pressure agent 2 is a 1,3,4-thiadiazole substituted derivative, which belongs to solid sulfide extreme pressure agents. It has good water resistance, increases the bearing capacity of the tooth surface under medium and heavy loads, and avoids the hydrolysis failure problem of some liquid extreme pressure agents caused by slurry leakage from the rod mill.
[0061] Metal powder: 2% to 3%, wherein the metal powder is a mixture of aluminum powder with a particle size of 10μm to 20μm and zinc powder with a particle size of 3μm to 4μm (mass ratio 2:1). The soft metal powder has a strong adsorption force, which can fill the pitting corrosion on the tooth surface, prevent the pitting corrosion from expanding and causing fatigue spalling, and can also adsorb and embed into fatigue cracks to avoid the occurrence of later fatigue pitting corrosion, effectively extending the service life of the equipment.
[0062] Rust inhibitor: 1% to 1.5%, wherein the rust inhibitor is one or a mixture of both of petroleum ester barium soap and zinc oxide.
[0063] Metal deactivator: 0.1% to 0.5%, wherein the metal deactivator is a benzotriazole derivative.
[0064] Tackifier: 12%–20%, wherein the tackifier is a metallocene-catalyzed ethylene-propylene copolymer NacoTac2008. The tackifier improves the kinematic viscosity of the base oil at 40°C to 3500–11000 mm⁻¹. 2 / s.
[0065] A method for preparing a special lubricating grease for rod mills, comprising the following steps:
[0066] 1) Premixed base oil: PAO100 and 150BS are introduced into the base oil premixing tank through a flow meter, and the temperature is controlled at 70-80℃. The mixture is premixed and stirred for 20-30 minutes.
[0067] 2) Thickening reaction: Transfer 60%–70% of the premixed base oil from step 1) into the reactor, add triisopropanol aluminum trioxide, start bidirectional stirring and bottom stirring, add stearic acid at 80–85℃, and maintain the temperature at 86–92℃ for 20–30 minutes. Add benzoic acid at 115–120℃, and maintain the temperature at 125–130℃ for 30–40 minutes.
[0068] This process uses a stepwise reaction method to prepare composite aluminum soap, in which stearic acid and benzoic acid react sequentially with triisopropanol aluminum oxo. The composite aluminum soap prepared by this method has a stronger thickening effect on the system.
[0069] 3) High-temperature refining: Heat the material from step 2) to 155-160℃, keep it at that temperature for 5-10 minutes, add the thickener NacoTac2008, stir for 15-20 minutes, transfer it from the homogenizer to the mixing tank to obtain high-viscosity composite aluminum soap.
[0070] In this process, the thickener NacoTac2008 is added at high temperature, and the material is treated with a homogenizer, which helps to disperse the polymer copolymer in the material and ensures that a uniform high viscosity system is obtained.
[0071] 4) Melting microcrystalline wax: Control the temperature of the material in step 3) to 100-105℃, add microcrystalline wax, and stir to melt for 20-25 minutes.
[0072] In this process, microcrystalline wax is added at a temperature 20°C above its melting point, resulting in a finished product with a delicate and glossy appearance and optimal water resistance.
[0073] 5) Dispersing solids: Cool the material from step 4) to 85-90℃, add solid extreme pressure agent 1 and solid extreme pressure agent 2, stir and mix, and filter step by step (80 mesh for 10-15 minutes, 100 mesh for 15-20 minutes, 150 mesh for 20-30 minutes).
[0074] This process requires that solid extreme pressure agent 2 be added after solid extreme pressure agent 1 is evenly dispersed, and a step-by-step filtration method should be used to avoid the simultaneous addition of the two agents, which would cause material aggregation and adhesion, affecting the appearance and extreme pressure performance.
[0075] 6) Mixed protective agent: Control the temperature of the material in step 5) to 80-85℃, add rust inhibitor and metal deactivator, and stir for 10-15 minutes.
[0076] 7) Add metal powder: Cool the material from step 6) to 30-50℃, add metal powder, and at the same time add the remaining premixed base oil in the form of spray from the top of the kettle. Mix and stir for 10-15 minutes, and filter through a 150-mesh filter for 30-40 minutes.
[0077] The purpose of this step is to control and reduce the concentration of metal powder mixed with air in the reactor, considering that the addition of metal powder will cause suspension in the reactor, and to prevent the metal powder from reaching the concentration of deflagration. For safety reasons, the temperature in the reactor is set to drop to 30-50°C, aluminum and zinc powder are added, and at the same time, the remaining premixed oil is sprayed into the oil injection port at the top of the reactor to suppress powder suspension and ensure production safety.
[0078] 8) Degassing and Packaging: Transfer the material from step 7) to a degassing reactor for degassing (pressure -0.07 to -0.09 MPa) and packaging.
[0079] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0080]
Example
[0081] During long-term production, the vibration of the steel bars inside the cylinder of the rod mill causes the cylinder bolts to loosen, which in turn causes deformation of the sealing rubber and sealing ring rolls, resulting in seal failure. The slurry leaks into the gear cover, destroying the contact oil film of the large and small gears. Particulate matter wears on the tooth surface, causing tooth surface damage, fatigue cracks, and wear pitting. In addition, the tooth bottom surface is in long-term contact with the slurry, and the rust prevention performance of the lubricating grease is insufficient, which in turn leads to tooth surface corrosion.
[0082] The specific components and component contents (by mass percentage) of the special lubricating grease for open gears of rod mills provided in Examples 1-8 are shown in Table 1 (where “-” indicates that the component was not added in this example):
[0083] Table 1
[0084]
[0085] The preparation methods of the special grease for open gears of rod mills provided in Examples 1-8, and the process parameters of steps 1)-7) are shown in Table 2:
[0086] Table 2
[0087]
[0088]
[0089] Product performance testing: The rod mill greases prepared in the eight examples were tested and evaluated using the following testing equipment.
[0090] The test results are shown in Table 3:
[0091] Table 3
[0092]
[0093] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A special lubricating grease for open gears of rod mills, characterized in that, The lubricating grease comprises, by weight percentage: Base oil: 55%–65%; the base oil is a mixture of paraffinic base oil and polyalphaolefin base oil, with a kinematic viscosity of 700–850 mmHg at 40°C. 2 / s; Fatty acid: 1.05%~1.47%; it is stearic acid with a melting point of 69~72℃; Aromatic acid: 0.45%~0.63%; the aromatic acid is benzoic acid with a melting point of 122~123℃; Trimer: 0.86%–1.21%; the trimer is triisopropanol aluminum trioxide; Solid wax: 2%–3%; solid wax is microcrystalline wax with a melting point of 80–85℃; Solid extreme pressure agent 1: 10%~13%; Solid extreme pressure agent 1 is S-0 flake graphite with a particle size <1μm; Solid extreme pressure agent 2: 1%–2%; Solid extreme pressure agent 2 is a 1,3,4-thiadiazole substituted derivative; Metal powder: 2-3%; the metal powder is a mixture of aluminum powder with a particle size of 10μm-20μm and zinc powder with a particle size of 3μm-4μm in a mass ratio of 2:1; Rust inhibitor: 1%~1.5%; the rust inhibitor is one or a mixture of petroleum ester barium soap and zinc oxide; Metal deactivator: 0.1%–0.5%; the metal deactivator is a benzotriazole derivative; Tackifier: 12%–20%; the tackifier is metallocene-catalyzed ethylene-propylene copolymer NacoTac2008; The method for preparing lubricating grease includes the following steps: 1) Premixed base oil: Paraffinic base oil and polyalphaolefin base oil are introduced into the base oil premixing tank through a flow meter, and the temperature is controlled at 70-80℃. The mixture is premixed and stirred for 20-30 minutes. 2) Thickening reaction: Transfer 60% to 70% of the premixed base oil into the reactor, add trimer, start bidirectional stirring and bottom stirring, add fatty acids at 80 to 85°C, keep the temperature at 86 to 92°C for 20 to 30 minutes, add aromatic acid at 115 to 120°C, keep the temperature at 125 to 130°C for 30 to 40 minutes. 3) High-temperature refining: Heat the material from step 2) to 155-160℃, keep it at that temperature for 5-10 minutes, add the thickener, stir for 15-20 minutes, transfer it from the homogenizer to the mixing tank to obtain high-viscosity composite aluminum soap. The dynamic viscosity of the high-viscosity composite aluminum soap is 6000-20000 mPa.s. 4) Melting microcrystalline wax: Control the temperature of the material in step 3) to 100-105℃, add microcrystalline wax, and stir to melt for 20-25 minutes; 5) Dispersing solids: Cool the material from step 4) to 85-90°C, add solid extreme pressure agent 1 and solid extreme pressure agent 2, stir and mix, and filter step by step; 6) Mixing protective agents: Cool the material from step 5) to 80-85℃, add rust inhibitor and metal deactivator, and stir for 10-15 minutes; 7) Add metal powder: Cool the material from step 6) to 30-50℃, add metal powder, and at the same time add the remaining premixed base oil by spraying it from the top of the kettle. Mix and stir for 10-15 minutes, and filter through a 150-mesh filter for 30-40 minutes. 8) Degassing and Packaging: Transfer the material from step 7) to the degassing kettle for degassing and packaging.
2. The special lubricating grease for open gears of rod mills according to claim 1, characterized in that, Step 5 of the preparation method: step-by-step filtration operation, 80 mesh filtration for 10-15 minutes, 100 mesh filtration for 15-20 minutes, and 150 mesh filtration for 20-30 minutes.
Citation Information
Patent Citations
High-speed chain lubricating grease and preparation method thereof
CN102965178A
Heavy-load open-type gear lubricating grease and preparation method thereof
CN104164277A
Antirust high-temperature lubricating grease composition
CN104164280A
